2021
DOI: 10.1111/jasp.12844
|View full text |Cite
|
Sign up to set email alerts
|

Blaming others for their illness: The influence of health‐related implicit theories on blame and social support

Abstract: Some people believe that their own health is rather malleable and can be changed (incremental theory), whereas other people believe that their health is relatively fixed (entity theory). Previous research suggests that individuals who hold a strong incremental theory of health have more positive health‐related attitudes and engage in more health‐promoting behaviors in everyday life. However, less is known about the interpersonal effects of an incremental theory of health. A strong incremental theory of health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 74 publications
4
21
0
Order By: Relevance
“…Further, we consistently observed that blame was negatively linked to helping intentions and that outcome expectancy was positively linked to helping intentions. As a consequence, blame and outcome expectancy were parallel mediators of the relationship between mindsets and helping intentions, as predicted by the DUPA-Model (Dohle et al, 2022). As these two mediators act in opposite directions, they can cancel each other out, resulting in total null effects, as observed across all studies.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Further, we consistently observed that blame was negatively linked to helping intentions and that outcome expectancy was positively linked to helping intentions. As a consequence, blame and outcome expectancy were parallel mediators of the relationship between mindsets and helping intentions, as predicted by the DUPA-Model (Dohle et al, 2022). As these two mediators act in opposite directions, they can cancel each other out, resulting in total null effects, as observed across all studies.…”
Section: Discussionmentioning
confidence: 63%
“…Our findings contribute to the literature on mindsets by highlighting the existence and relevance of their interpersonal consequences. Going beyond earlier work that demonstrated such consequences in the domain of health or education (e.g., Dohle et al, 2022;Yeager et al, 2022), our work demonstrated such consequences in the domain of poverty, an area that has only recently caught the attention of mindset researchers (Zhao, Chen, et al, 2021;. Furthermore, going beyond simply demonstrating such interpersonal MINDSETS OF POVERTY 20 consequences, we tested a specific social-cognitive model (the DUPA-Model, Dohle et al, 2022).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations